2022
DOI: 10.1093/eurheartj/ehac322
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk score for ACE-inhibitor-associated cough based on the discovery of new genetic loci

Abstract: Aims To search for sequence variants associated with ACEi discontinuation and to test their association with ACEi-associated adverse drug reactions (ADRs). Methods and results A genome-wide association study (GWAS) on ACEi discontinuation was conducted, including 33 959 ACEi-discontinuers and 44 041 controls. Cases were defined as persons who switched from an ACEi treatment to an angiotensin receptor blocker. Controls were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 56 publications
0
13
1
Order By: Relevance
“…After genotyping, the presence of at least one risk allele in any of the two variants was considered a high-risk factor for ACEI-related cough. The association of NTSR1 SNP (rs6062847), reported in a recent European study [9], and cough was not significant in our previous study [10]. Furthermore, the frequency of CLASP1 SNP (rs62151109), which had a strong association with cough in a Swedish population [11], was 0 in Koreans.…”
Section: Methodscontrasting
confidence: 64%
See 1 more Smart Citation
“…After genotyping, the presence of at least one risk allele in any of the two variants was considered a high-risk factor for ACEI-related cough. The association of NTSR1 SNP (rs6062847), reported in a recent European study [9], and cough was not significant in our previous study [10]. Furthermore, the frequency of CLASP1 SNP (rs62151109), which had a strong association with cough in a Swedish population [11], was 0 in Koreans.…”
Section: Methodscontrasting
confidence: 64%
“…With recent advances in genetic research [8], several genome-wide association studies (GWASs) have reported genetic loci associated with ACEI-related cough. Candidate genes include NTSR1 [9], NELL1 [10], and CLASP1 [11].…”
Section: Introductionmentioning
confidence: 99%
“…These 11 SNPs were included in the main Asian population analysis ( Supplementary Table S3 ). Additionally, we selected seven SNPs from a published European GWAS ( Ghouse et al, 2022 ) and extracted correlations between SNPs and exposure relevant to the European population. These seven SNPs were included in the main European population analysis ( Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…We selected single nucleotide polymorphisms (SNPs) related to ACE inhibition and ACEI-induced cough from previous genome-wide association studies (GWAS) for use as genetic proxies for exposure. The whole-genome detection of ACE inhibition was obtained from a previous study, ( Yarmolinsky et al, 2022 ), and SNPs related to ACEI-induced cough in the European population were obtained from a meta-analysis ( Ghouse et al, 2022 ) of three independent European cohorts. Additionally, SNPs related to ACEI-induced cough in the Asian population were sourced from 396 Chinese individuals ( Mu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that while we have made certain genomic insights regarding the adverse effects (e.g., drug resistance) of first-generation NTRK inhibitors, more reliable conclusions about causality may require higher-level genetic evidence in the future. This could involve identifying single nucleotide polymorphism (SNP) loci significantly associated with ADEs through genome-wide association studies ( Ghouse et al, 2022 ; Giles et al, 2022 ). Such an approach could enable the screening and identification of patients susceptible to adverse effects, thereby improving efficacy and concurrently mitigating adverse effects.…”
Section: Discussionmentioning
confidence: 99%